A Tribute to James Moffett - Miles Myers; Donald R. Gallehr; Richard L. Graves; Regina Foehr; Sheridan Blau; Betty Jane Wagner (Journal of the Assembly for Expanded Perspectives on Learning, 1997)
A tribute to James Moffett, a visionary and trailblazer, who wrote about trends in education long before others even considered their possibilities.